ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN MINAT WUS MENGGUNAKAN ALAT KONTRASEPSI DALAM RAHIM - Aisyah Aisyah; Eny Sendra; Emi Kusumawardani; Rina Marlina Manalu (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Women of Reproductive Age (WRA) are women between the ages of 15 and 49, a period during which their reproductive organs have fully developed and they are capable of becoming pregnant. The purpose of this study was to analyze factors associated with WRA’s interest in using intrauterine devices (IUDs). This study employed a cross-sectional design. The study was conducted in the service area of the Siulak Mukai Community Health Center. The study was carried out in July 2025. The sample consisted of 60 participants. Simple random sampling was used. A research questionnaire was used as the research instrument. Data analysis was performed using univariate and bivariate methods. The results showed an association between parity (p-value: 0.030) and spousal support (p-value: 0.000) and the interest of women of reproductive age in using intrauterine devices. It is recommended that community health centers conduct outreach on IUDs by providing more in-depth health education and counseling so that women of reproductive age in the region will be interested in choosing to use IUDs.Keywords: Spousal Support, Parity, Women of Childbearing Age.